The gender turnaround: Young women now travelling more than young men. (June 2016) - Tilley, Sara; Houston, Donald
Abstract: Daily travel mobility is on a downward trend in several developed economies, including the UK. This paper examines how mobility trends are differentiated by gender and birth cohort. Over the last decade, young adult women in Britain have come to have greater weekly mobility than their male counterparts. Until recently, women have consistently had lower mobility than men - suggesting that this finding could be a significant break with the past. This gender turnaround is driven mainly by young men travelling substantially less today than previous generations of young men. We find that younger cohorts of women travel are travelling further as they age, whilst younger cohorts of men are no longer becoming more mobile as they approach early mid-life, traditionally a life course peak in travel mobility. Possible reasons for the greater mobility of young women than young men are discussed and areas for future research identified. Highlights: We examine changes in the mobility trends by gender and birth cohort in Britain. Young women now travel more than young men, a significant break with the past. Young men travel substantially less today than previous generations of young men. Birth cohorts face different socio-economic contexts which impact mobility trends.